THE FOLDING PARADIGM: DRIVING PACKAGING INNOVATION THROUGH STRUCTURAL ENGINEERING, KINEMATICS, AND MATERIAL INTELLIGENCE - Ping, Hu; Yatsenko, Maryna Volodymyrivna (Theory and practice of design, 2025)
Abstract. The purpose of this paper is to establish the “folding paradigm” – the application of structurally engineered origami and folding principles – as a critical and underexplored driver of contemporary packaging innovation. It argues that this paradigm fundamentally shifts the focus of design from surface aesthetics and material selection to the inherent value created by a package’s geometric structure, kinematic behavior, and functional integration. Methodology. The research employs a qualitative, multiple-case study methodology. A selection of eight diverse and innovative packaging designs is systematically analyzed. The analytical framework assesses each case against core principles of the folding paradigm, including engineered structural integrity, controlled kinematics, seamless feature integration, and material-structure interaction. Results. The analysis reveals that the folding paradigm creates value by systematically engineering a package’s structure. This approach drives innovation across five key dimensions: it achieves Functional Transformation by embedding secondary uses; elevates the User Experience by transforming unboxing into a memorable ritual; enables Inherent Functional Integration of features into a monolithic form; realizes Systemic Efficiency in materials and logistics; and facilitates Tangible Brand Expression, allowing the physical structure itself to communicate a compelling brand story. Scientific novelty. This paper provides a comprehensive theoretical framework and practical analysis of a structural-first approach to packaging design. It moves beyond the conventional discourse on materials and graphics to position geometric and mechanical ingenuity as a primary force for creating intelligent, efficient, and meaningful packaging solutions that address key challenges in sustainability, user engagement, and market differentiation. Practical relevance. The “folding paradigm” was established as a practical design methodology, demonstrated through a portfolio of eight innovative case studies showcasing principles of functional transformation, controlled kinematics, and monolithic integration. The findings offer actionable insights for designers, engineers, and brand managers, providing strategies to create intelligent, efficient, and meaningful packaging solutions.